Media Sosial sebagai Jembatan Informasi dan Empowering Petani dan Sistem Pangan Global - Suprihandari, Miya Dewi (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
Social media has great potential to empower farmers in Indonesia by providing greater access to information and connecting them directly with the market. This technology helps farmers gain market knowledge and farming practices more efficiently while reducing dependence on middlemen. However, challenges such as limited internet infrastructure and low digital literacy still hinder optimal utilization. This research used a qualitative approach with an exploratory case study. Data was collected through in-depth interviews with farmers who use social media, an online survey of farming communities, and content analysis on digital platforms. This method aims to understand how digital technology supports farmers in diverse socio-economic contexts. Results show that social media improves market access, transparency and distribution efficiency, thereby strengthening the position of smallholder farmers in the food system. However, optimizing its benefits requires the support of adequate internet infrastructure and digital literacy training. With these steps, social media can be an effective tool to empower farmers, improve their welfare, and create a more inclusive and sustainable food system.